Disproportionality analysis of European safety reports on autoimmune and rheumatic diseases following COVID-19 vaccination - Federica Fraenza; Cecilia Cagnotta; Mario Gaio; Liberata Sportiello; Cristina Scavone; Annalisa Capuano; Ugo Trama (Scientific Reports)
Abstract The safety profile of COVID-19 vaccines is well-established, yet the widespread immunization campaign has led to an increase in reported cases of Immune-Mediated and Rheumatic Diseases (IMDRs). This study aimed to assess the reporting of Adverse Events Following Immunization (AEFIs) related to IMDRs after COVID-19 vaccination. We analyzed all individual case safety reports (ICSRs) related to COVID-19 vaccines authorized in the European Union (i.e., tozinameran, elasomeran, ChAdOx1-S NCoV-19, and Ad26.Cov2.S) registered in the EudraVigilance (EV) database from January 1, 2021, to October 23, 2023. Our analysis identified ICSRs with events indicative of IMDRs and conducted disproportionality analysis (i.e., Reporting Odds Ratio (ROR) with 95% CI) to examine the frequency of different IMDR types linked to each vaccine. In total, 45,352 ICSRs reported at least one AEFI associated with rheumatic or autoimmune conditions, with 54% of them implicating tozinameran as the suspected vaccine. More than half of the reported AEFIs were classified as serious, with approximately 45% remaining unresolved. The most frequently reported conditions were other immune-mediated diseases, followed by arthritis, vasculitis, systemic lupus erythematosus, and tendinopathies. Our disproportionality analysis suggested that mRNA vaccines may be more frequently associated with new autoimmune rheumatic diseases. Stratified analysis revealed significant associations for ChAd, particularly in vasculitis and tendinopathies, only when compared to Ad26.Cov2.S. Real-world pharmacovigilance data suggest that autoimmune and rheumatic diseases may be under-reported following COVID-19 vaccination, highlighting the need for further research to better understand the underlying mechanisms. The findings from this disproportionality analysis suggest the need for further studies to investigate these results in greater depth.